An investigation into the underrepresentation of women in the Pilbara mining region of Western Australia - Kljajevic, Bobana (Curtin University, 2015)
This study found that while women are not deterred from working in non-traditional roles, mining companies have not succeeded in disrupting a patriarchal organisational culture that continues to permit discriminatory attitudes. This has resulted in middle management privileging a certain type of worker (male), with women having difficulty attaining promotional opportunities and working within more senior roles. It is argued that such attitudes are the product of the wider gender order operating within gendered institutions.